KELUARGA SAKINAH ALUMNI PESANTREN TAHFID: - Mahmudz Mahmudz; Iksan Iksan (SHAKHSIYAH BURHANIYAH: Jurnal Penelitian Hukum Islam, 2021)
This article is a result of a qualitative field research. This article discusses efforts to form a sakinah family. The research location is Jombang Regency. The data of this research are alumni of Madrasatul Qur'an Islamic boarding school Tebuireng Jombang who are domiciled in Jombang Regency. This study concludes that marriage counseling to maintain household harmony, one of which can be done independently through istiqamahan interacting with the Qur'an. This argument is based on data from the family of alumni who have memorized the Koran PP. Madrasataul Qur'an Tebuireng in Diwek district, Jombang. The alumni practice the routine of memorizing the Qur'an, always remembering Allah (taqarrub), tadarus Al-Qur`an every day, praying in congregation, being open between family members. The alumni carry out several family functions, namely educational, religious, protective, economic, and recreational functions. Keywords: marriage counseling, happy family, pesantren alumni. DAFTAR PUSTAKA Abdurrab Nawabuddin, Kaifa Tahfazhul Qur`an. Abi Daud, Sunan Abi Daud. Jilid 1, Dar al-Fikr, Mesir, 1990, h. 327, no. hadits: 1455 Ahsin W Al Hafidz, Bimbingan Praktis Menghafal Al-Qur`an. Amin, H. A., Masrokhin, M., & Anwar, K. (2021). GUARDIANS CONCEPT IN QUR’AN PERSPECTIVE . SHAKHSIYAH BURHANIYAH: Jurnal Penelitian Hukum Islam , 6(1), 95 - 114. https://doi.org/10.33752/sbjphi.v6i1.1642 Departemen Agama Republik Indonesia, Al-Qur`an dan Terjemahan, Yayasan Penyelenggara Penterjemah/ Pentafsir Alquran (Jakarta, 2001). Departemen Agama Republik Indonesia, Al-Qur‟an dan Terjemahan, Yayasan Penyelenggara Penterjemah/ Pentafsir Alquran (Jakarta, 2001) Hadist, Shahih Muslim, No. 4803 J.R. Raco, Metode Penelitian Kualitatif: Jenis, Karakteristik dan Keunggulannya Lexy J. Moleong, Metodologi Penelitian Kualitatif. Marzuki, Metodologi Riset, (Yogyakarta: Prasetia Widia Pratama Yogyakarta, 2000). Nasution, Metode Research: Penelitian Ilmiah, (Bandung: Jemmars, 1991) Quraish Shihab, Mukjizat Al-Qur`an (Ditinjau dari Aspek Kebahasaan, Aspek Ilmiah dan Pemberitahuan Ghaib), (Bandung: Mizan, 1997). Wawancara dengan Bapak Abdullah Tamam (Kamis, 28 Juni 2018) Wawancara dengan Bapak H. Ali Said, M.HI (Selasa, 26 Juni 2018) Wawancara dengan Bapak K.H. Ahmad Syakir Ridlwan, Lc, M.HI (Rabu, 27 Juni 2018) Wawancara dengan Bapak K.H. Muhammad Fauzan Kamal, S.Ag dan Ibu Nyai Naili Nur Fadhilah (26 Jumi 2018) Zaitunah Subhan, Membina Keluarga Sakinah, (Yogyakarta: Pustaka Amani, 2004), H. 6.